New Conversives in the English Scientific and Technological Sphere - Kiyko, Svitlana; Rubanets, Tetiana (Educator, 2023)
English as a language of analytical system has a great creative power for the development of conversion, which is highly productive way of word formation. In the framework of transposition theory, we regard the interpretation of conversion as a morphological transposition with a word-forming character. The topic of our study are the new conversives in the English scientific and technological sphere. For the study, 572 examples of neologisms were selected from the dictionaries "The Facts on File Dictionary of New Words", "The Morrow Book of New Words", which presents neologisms of the 1950-1970s, as well as "The Oxford Dictionary of New Words" and "Webster's New World Dictionary of American English", which provide neologisms of the early twenty-first century. The research shows that conversives to denote new concepts in the space industry prevailed in the 50-70s of the last century, while new developments in the field of science and new technologies are more typical for the beginning of the XXI century. The field of science and new technologies has a higher number of new conversives (86.7%), while the field of space exploration has the lowest growth of conversives (13.3%). Given the uneven distribution of conversives, it can be concluded that conversion is not only one of the ways of replenishing the vocabulary of the language, but also a mean of reflecting the conceptual picture of the world of the English-speaking society at a certain historical period.
Keywords: англійська мова; конверсія